Alternative splicing reprogramming in fungal pathogen Sclerotinia sclerotiorum at different infection stages on Brassica napus - Cheng, Xiaohui; Zhao, Chuanji; Gao, Lixia; Zeng, Lingyi; Xu, Yu; Liu, Fan; Huang, Junyan; Liu, Lijiang; Liu, Shengyi; Zhang, Xiong (Frontiers in Plant Science, 2022)
Alternative splicing (AS) is an important post-transcriptional mechanism promoting the diversity of transcripts and proteins to regulate various life processes in eukaryotes. Sclerotinia stem rot is a major disease of Brassica napus caused by Sclerotinia sclerotiorum, which causes severe yield loss in B. napus production worldwide. Although many transcriptome studies have been carried out on the growth, development, and infection of S. sclerotiorum, genome-wide AS events of S. sclerotiorum remain poorly understood, particularly at the infection stage. In this study, transcriptome sequencing was performed to systematically explore the genome-scale AS events of S. sclerotiorum at five important infection stages on susceptible oilseed rape cultivar. A total of 130 genes were predicted to be involved in AS from the S. sclerotiorum genome, among which 98 genes were differentially expressed and may be responsible for AS reprogramming for its successful infection. In addition, 641 differential alternative splicing genes (DASGs) were identified during S. sclerotiorum infection, accounting for 5.76% of all annotated S. sclerotiorum genes, and 71 DASGs were commonly found at all the five infection stages. The most dominant AS type of S. sclerotiorum was found to be retained introns or alternative 3’ splice sites. Furthermore, the resultant AS isoforms of 21 DASGs became pseudogenes and 60 DASGs encoded different putative proteins with different domains. More importantly, 16 DASGs of S. sclerotiorum were found to have signal peptides and possibly encode putative effectors to facilitate the infection of S. sclerotiorum. Finally, about 69.27% of DASGs were found to be non-differentially expressed genes, indicating that AS serves as another important way to regulate the infection of S. sclerotiorum on plants besides gene expression level. Taken together, this study provides a genome-wide landscape for the AS of S. sclerotiorum during infection as well as an important resource for further elucidating the pathogenic mechanisms of S. sclerotiorum.